MODERNIZATION OF XINJIANG UYGHUR AUTONOMOUS REGION AND ITSIMPACT ON TRANSBOUNDARY RELATIONSHIPS KAZAKHSTAN AND CHINA - Khadzhieva Gulzhahan Usmanovna; Eleonora Tankova (Scientific Journal of Pedagogy and Economics, 2019)
For nearly two decades, XUAR has been the vanguard in the implementation of the program of largescale development of the western regions of the PRC. The article discusses the internal and external causes that determine the special role of the studied national region in the Chinese regional politics. The undeniable advantage of Xinjiang Uyghur Autonomous Region (XUAR) is its geographical location. That on XUAR accounted for 1/4 of the Chinese state land border, and it borders with the largest number of foreign countries (in comparison with other autonomous regions) determines the importance of its place in geostrategic plans of China. This geographical position allows to activate the policy of "going outside", that is, the policy of expansion and intensification international trade and economic relations of the country Central Asian, and further in the European direction, forcing course "East accumulates, the West exports." Focus in the article is devoted to dynamic changes in the socioeconomic development of the area as a result of the strategy being implemented. As a result, the study justifies the unique place of XUAR in China’s cross-border relationship with Kazakhstan. Accelerated development of XUAR is an important factor influencing the Kazakh-Chinese cooperation in trade, energy, transport infrastructure, safety, ecology, culture. Moreover, without the factor of XUAR it is impossible to design a holistic system of development of Central Asian region.